Stem Cells in Spinal Cord Injury - Wrathall, Jean R. (IOS Press, 2008)
Traumatic injury to the adult spinal cord results in a massive loss of cells and permanent functional deficits. However, recent studies demonstrate that there is a proliferative response of endogenous glial precursors and progenitors and perhaps also pluripotent neural stem cells. These cells may prove to be an important new therapeutic target to improve recovery after injury to the spinal cord and brain.